1997
DOI: 10.1164/ajrccm.155.4.9105070
|View full text |Cite
|
Sign up to set email alerts
|

Objective predictors of response for staple versus laser emphysematous lung reduction.

Abstract: Recently described surgical approaches to the treatment of emphysema, including buttressed stapled volume reduction and laser coagulation, are associated with variable clinical outcomes. We examined objective preoperative factors as predictors of response to treatment in patients enrolled in a randomized trial of staple versus laser volume-reduction surgery in order to help define patient selection criteria for these procedures. Seventy-two patients with severe symptomatic emphysema without bullae were entered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Indeed, although several factors were shown to be significantly related to response, the models, in general, only explain a relatively limited fraction of the variance such that they do not allow proper prediction of the response in an individual patient. Indeed, BRENNER et al [93] analysed the variables related to response in a study comparing buttressed stapled resections with laser coagulation. Buttressed stapled resections were clearly more effective than laser coagulation.…”
Section: Selection Of Candidatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, although several factors were shown to be significantly related to response, the models, in general, only explain a relatively limited fraction of the variance such that they do not allow proper prediction of the response in an individual patient. Indeed, BRENNER et al [93] analysed the variables related to response in a study comparing buttressed stapled resections with laser coagulation. Buttressed stapled resections were clearly more effective than laser coagulation.…”
Section: Selection Of Candidatesmentioning
confidence: 99%
“…They are summarised in table 4. For the clinical criteria, age w75-80 yrs is usually associated with poor outcome [64,93], although this has been debated in other studies [95]. Severe comorbidity is usually considered to be an exclusion criterion.…”
Section: Selection Of Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…LVRS has been shown to benefit some patients with advanced emphysema [2][3][4][5][6][7], but studies have shown a wide range of individual outcomes [2,5,6,[8][9][10][11][12][13]. More recently, bronchoscopic lung volume reduction (BLVR) procedures have been investigated that aim to induce significant volume reduction in the most diseased lobe(s) [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…This should not obscure the fact that up to 20% of the patients do not experience an improvement either subjectively or in the pulmonary function tests [4, 39, 41, 42, 45±48, 51, 52, 54, 57, 61, 62] and that mortality is not negligible [4,39,40,43,47,49,50,52,54,58,99], reaching 10% in some series [49]. The determinants of outcome have not yet received much attention.…”
Section: Future Prospectsmentioning
confidence: 99%